Do Brand Image and Brand Trust Mediate the Effect of Service Quality on Brand Loyalty? Lessons from Higher Education Sector - Milcha Handayani Tammubua (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This study analyzes the relationship between service quality on brand image, brand trust, and brand loyalty in the higher education sector. This study used a 4-point Likert scale questionnaire to collect the data from 185 students at the Distance Learning Program Unit Universitas Terbuka Jayapura registered in 2014-2018. It also employed the Structural Equation Modeling Partial Least Square (SEM-PLS) method to analyze the data with the help of SmartPLS 3 software. The results showed that service quality positively and significantly affected the brand image, brand trust, and brand loyalty. Brand trust has a positive and significant effect on brand loyalty, while the brand image has no significant effect on brand loyalty.